Stable production method for functional fine particles having radically polymerizable groups introduced via urethane bonds
By using urethane bonds to introduce radically polymerizable groups into inorganic fillers, the method addresses the limitations of previous silane coupling agents, achieving high mechanical strength and durability in medical and dental materials.
Patent Information
- Application Number
- JP2023169722
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-10
AI Technical Summary
Existing silane coupling agents used to introduce radically polymerizable groups into inorganic fillers via hydrolysis and condensation are limited by a maximum drying temperature of about 150°C, resulting in incomplete dehydration and condensation, which leads to fragile xerogel layers and insufficient mechanical strength.
The introduction of radically polymerizable groups into the surface of inorganic fillers is achieved through urethane bonds formed by reacting the hydroxy groups on the filler surface with organic compounds that generate isocyanate groups upon heating, eliminating the fragile xerogel layer and providing a strong covalent bond.
This method allows for the production of functional fine particles with high mechanical strength and durability, overcoming the limitations of previous technologies by ensuring complete surface modification without fragile xerogel layers.
Smart Images

Figure 2025059564000001 
Figure 2025059564000002 
Figure 2025059564000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for stably producing functional fine particles having radically polymerizable groups introduced therein via urethane bonds. [Background technology]
[0002] In the medical and dental fields, metal prostheses and synthetic resin moldings are used to repair bone and tooth defects. Adhesives containing adhesive polymerizable monomers are often used to bond them to biological hard tissues. In the field of conservation and restoration, a curable composition called a composite resin is used in clinical practice every day. This is done by filling an uncured (before radical polymerization) paste into a tooth or other defective part and then applying external energy such as light irradiation to obtain a radically polymerized cured product. Generally, these adhesives and composite resins use (meth)acrylic acid derivative monomers such as methyl methacrylate, triethylene glycol dimethacrylate, and urethane dimethacrylate. In the free radical polymerization (hereinafter referred to as radical polymerization) of vinyl monomers such as these (meth)acrylic acid derivative monomers, the carbon-carbon double bond is cleaved to become a single bond, forming a polymer and curing. In addition to vinyl monomers, inorganic fillers are added to this composite resin for the purpose of improving mechanical strength. In general, these inorganic fillers are surface-treated with a silane coupling agent having a polymerizable group to improve wettability and mechanical strength.
[0003] In the dental field, γ-methacryloxypropyltrimethoxysilane (hereinafter referred to as KBM-503) has been widely used as a silane coupling agent. When particles surface-treated with this compound are used, the inorganic filler surface is indeed hydrophobized by the surface treatment, and some improvement in mechanical strength is observed. However, since these silane coupling agents have a radical polymerizable group in the carbon skeleton, the drying temperature after surface treatment is limited to about 110°C. Here, the alkoxy group of the silane coupling agent is hydrolyzed, and the silanol group generated thereafter undergoes dehydration condensation to form a polysiloxane bond. A high drying temperature is effective in promoting this dehydration condensation. If sufficient dehydration condensation is not performed, the generated silanol group remains in a xerogel state, and sufficient mechanical strength cannot be obtained. To explain in more detail, the silanol group on the filler surface and the silanol group generated by dealcoholization of the silane coupling agent are chemically strongly bonded by dehydration condensation. This dehydration condensation generally proceeds spontaneously, but when the reaction points are far apart, molecular vibration due to heating is required. It goes without saying that higher heating is required for dehydration condensation between reaction points that are far apart. However, as mentioned above, silane coupling agents having radical polymerizable groups undergo polymerization at high temperatures exceeding 150°C and lose their function as silane coupling agents. Therefore, the upper limit of the heating temperature is limited, and as a result, a fragile xerogel layer remains, resulting in a decrease in mechanical strength. This problem was unavoidable as long as a silane coupling agent that introduces radical polymerizable groups into inorganic fillers by hydrolysis and condensation of alkoxy groups is used. In order to alleviate the fragility, a method using a silane coupling agent with a long alkyl chain (Patent Documents 1 and 2), a method using a silane coupling agent having a fluoroalkylene group (Patent Document 3), and a method using a silane coupling agent having many polymerizable groups (Patent Document 4) have been proposed. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 2-134307 [Patent Document 2] Japanese Patent Application Publication No. 3-70778 [Patent Document 3] Patent Publication No. 2007-238567 [Patent Document 4] Patent Publication No. 2010-229054 Summary of the Invention [Problem to be solved by the invention]
[0005] Silane coupling agents that introduce radical polymerizable groups into inorganic fillers by hydrolysis and condensation of alkoxy groups undergo dehydration and condensation of the silanol groups generated after hydrolysis to form polysiloxane bonds. A high drying temperature is effective in promoting this dehydration and condensation. If the dehydration and condensation is not sufficient, the generated silanol groups remain in a xerogel state, and sufficient mechanical strength cannot be obtained. In addition, the xerogel exhibits hydrophilicity. However, since the silane coupling agent has a radical polymerizable group of the carbon skeleton, the drying temperature after surface treatment is limited to about 150°C or less. Therefore, dehydration and condensation are not sufficiently performed, and the silanol groups remain, resulting in hydrophilicity. Therefore, in order to increase hydrophobicity, a method of using a silane coupling agent with a long alkyl chain (Patent Documents 1 and 2), a method of using a silane coupling agent with a fluoroalkylene group (Patent Document 3), and a method of using a silane coupling agent with many polymerizable groups (Patent Document 4) have been proposed. However, when the methods described in Patent Documents 1 to 3 are applied to dental materials, there is still room for improvement in mechanical strength. In addition, when the method described in Patent Document 4 was applied to dental materials, the durability of the materials was insufficient. Thus, the compatibility of durability and mechanical strength of materials using silane coupling agents in the conventional technology was insufficient, and there was room for further improvement. However, as mentioned above, it had to be said that it was scientifically difficult to achieve this with the conventional technology. The present invention aims to provide a stable production method for functional fine particles in which radical polymerizable groups are introduced to the surface of an inorganic filler via a urethane bond. [Means for solving the problem]
[0006] As a result of the inventors' earnest research, functional fine particles obtained by reacting a hydroxy group on the surface of an inorganic filler with an organic compound having a radical polymerizable group at one end and generating an isocyanate group by heating, through decomposition, are completely free of a fragile xerogel layer, and it is possible to introduce radical polymerizable groups to the surface of the inorganic filler through strong covalent bonds. This provides high mechanical strength and durability when used not only in medical and dental hardening compositions, but also in general industrial materials such as electronic industrial parts.
[0007] [ka]
[0008] The above is a schematic diagram of the surface modification of inorganic fillers using a silane coupling agent, which is a conventional technology. That is, the silane coupling agent is partially or completely dealcoholized and converted to a silanol group, and then dehydration condensation with the silanol group on the surface of an inorganic filler such as glass is performed to modify the surface. Due to the presence of reactive groups such as radical polymerizable carbon skeletons, dehydration condensation cannot be performed completely at high temperatures exceeding 150°C, and free silanol groups are also present.
[0009] In contrast, in the method for producing functional fine particles of the present invention, as shown below, silanol groups and isocyanate groups on the surface of inorganic fillers such as glass react with each other to reliably modify the surface through urethane bonds. Therefore, unlike the case where a silane coupling agent of the prior art is used, there is no fragile xerogel layer at all, and it is possible to introduce radical polymerizable groups to the surface of inorganic fillers through strong covalent bonds.
[0010] [ka]
[0011] The chemical structures before and after the heat treatment to obtain Chemical formula 2 are shown below.
[0012] [ka]
[0013] [ka] Effect of the Invention
[0014] The functional microparticles produced by the production method of the present invention have radical polymerizable groups introduced via urethane bonds to hydroxyl groups on the surface of the inorganic filler. These microparticles are completely free of the brittle xerogel layer that occurs when surface treatment is performed using a conventional silane coupling agent, and it is now possible to introduce radical polymerizable groups onto the inorganic filler surface via strong covalent bonds. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Examples of inorganic fillers used in the manufacturing method of the present invention include silicon dioxide, alumina, silica-titania, silica-titania-barium oxide, silica-zirconia, silica-alumina, lanthanum glass, borosilicate glass, soda glass, barium glass, strontium glass, glass ceramic, aluminosilicate glass, barium boroaluminosilicate glass, strontium boroaluminosilicate glass, fluoroaluminosilicate glass, calcium fluoroaluminosilicate glass, strontium fluoroaluminosilicate glass, barium fluoroaluminosilicate glass, strontium calcium fluoroaluminosilicate glass, etc. In particular, fluoroaluminosilicate barium glass, fluoroaluminosilicate strontium glass, fluoroaluminosilicate glass, etc., which are used in dental glass ionomer cement, resin-reinforced glass ionomer cement, resin cement, etc., can also be suitably used. The fluoroaluminosilicate glass referred to here has a basic skeleton of silicon oxide and aluminum oxide, and contains an alkali metal for introducing non-bridging oxygen. It further contains alkaline earth metals including strontium and fluorine as modifying and coordinating ions. It is also a composition in which a lanthanoid series element is incorporated into the skeleton to impart further X-ray opacity. The lanthanoid series element also participates in the composition as a modifying and coordinating ion depending on the composition range. These elements can be used alone or in combination of two or more kinds. Furthermore, the average particle size of the inorganic filler is preferably 0.001 to 100 μm, more preferably 0.001 to 10 μm. Furthermore, the shape of the inorganic filler may be either spherical or irregular.
[0016] The organic compound having a radical polymerizable group at one end and generating an isocyanate group upon heating is preferably selected from the following:
[0017] [ka]
[0018] [ka]
[0019] [ka]
[0020] As the organic compound having a radical polymerizable group at one end and generating an isocyanate group upon heating, which is used in the production method of the present invention, (E)-2-((((butan-2-ylideneamino)oxy)carbonyl)amino)ethyl methacrylate, 2-(3,5-dimethyl-1H-pyrazole-1-carboxamido)ethyl methacrylate, and (2,4-dioxo-1,3-diazetidine-1,3-diyl)bis(ethane-2,1-diyl) bis(2-methylacrylate) are particularly preferably used. These can be used alone or in combination of two or more kinds.
[0021] Examples of organic solvents used in the production method of the present invention include ethylene glycol monoethyl ether, ethylene glycol monoethyl ether acetate, ethylene glycol mono-n-butyl ether, ethylene glycol monomethyl ether, ortho-dichlorobenzene, xylene, cresol, chlorobenzene, isobutyl acetate, isopropyl acetate, isopentyl acetate, ethyl acetate, n-butyl acetate, n-propyl acetate, n-pentyl acetate, methyl acetate, cyclohexanone, N,N-dimethylformamide, tetrahydrofuran, 1,1,1-trichloroethane, toluene, n-hexane, methyl ethyl ketone, methyl cyclohexanone, and methyl n-butyl ketone, which may be used alone or in combination of two or more. EXAMPLES
[0022] The synthesis of the functional microparticles of the present invention in which radical polymerizable groups are introduced via urethane bonds to hydroxyl groups on the surface of an inorganic filler, and the preparation method and physical properties of the medical and dental hardenable composition containing the functional microparticles will be described in detail below, but the present invention is not limited to these descriptions in any way.
[0023] Examples 1 to 4 According to the example formulation table in Table 1, the functional particles of the present invention were synthesized, and then the medical and dental composite resin was prepared using them. OX-50 (manufactured by Nippon Aerosil Co., Ltd.) and Fuselex (manufactured by Tatsumori Co., Ltd.) were used as inorganic fillers. The specific method is described below. 40 mmol of each compound in the amount listed in the example formulation table in Table 1 was dissolved in 300 mL of dehydrated toluene, and added to a 500 mL eggplant flask containing 15.0 g of OX-50 and 40.0 g of Fuselex. Then, an electromagnetic stirrer was added and the mixture was stirred for 10 minutes, and further dispersed for 5 minutes using a 28 KHz-150 W ultrasonic disperser. After dispersion, the flask was immersed in an oil bath and refluxed for 5 hours. After reflux, the internal temperature was returned to room temperature, and a monomer liquid (UDMA, 2G, photopolymerization initiator) was added under light shielding, and after uniform stirring, the toluene and residues after heat treatment were distilled off using an evaporator. Then, toluene and residues after heat treatment were completely removed using a Thinky Planetary Vacuum mixer ARV-310 under conditions of 1000 rpm-5 KPa-15 min to obtain a medical and dental composite resin. The medical and dental composite resin thus obtained was prepared into a cured body according to ISO4049, and its bending strength was measured using an Instron universal testing machine (Instron 5567, Instron). Photopolymerization was performed by irradiating light for 30 seconds using Griplight II manufactured by Matsufu Co., Ltd. In order to determine the durability of the cured body, the cured body prepared in the same manner was immersed in 37°C distilled water for 24 hours, and then alternately immersed in a thermostatic water bath at 4°C and 60°C for 1 minute each, and the bending strength of the test body was measured.
[0024] Comparative Examples 1-2 The surface of OX-50 (Nippon Aerosil Co., Ltd.) and Fuselex (Tatsumori Co., Ltd.) were modified using the commercially available polymerizable silane coupling agent (Shin-Etsu Chemical Co., Ltd.) shown in Table 2, and a medical and dental composite resin was prepared using the modified surface. The specific surface modification method is described below. The type and amount of silane coupling agent shown in Table 2 was dissolved in 300 g of ethanol, and added to a 500 mL eggplant flask containing 15.0 g of OX-50 and 40.0 g of Fuselex. Then, an electromagnetic stirrer was added and the mixture was stirred for 10 minutes, and dispersed for 5 minutes using a 28 KHz-150 W ultrasonic disperser. After dispersion, 1.8 g of distilled water and 1.2 g of 1 wt% phosphoric acid aqueous solution were added while stirring, and the flask was immersed in a boiling water bath and refluxed for 5 hours. After the reflux was completed, the internal temperature was returned to room temperature, and the same monomer liquid (UDMA, 2G, photopolymerization initiator) as described in Table 1 was added under light shielding, and after uniform stirring, the ethanol was removed using an evaporator. The solvent was then completely removed using a Planetary Vacuum Mixer ARV-310 manufactured by Thinky under conditions of 1000 rpm-5 KPa-15 min to obtain a medical and dental composite resin. The medical and dental composite resin thus obtained was cured according to ISO4049, and the bending strength was measured using an Instron universal testing machine (Instron 5567, manufactured by Instron). The photopolymerization was performed by irradiating light for 30 seconds using Griplight II manufactured by Matsukaze Co., Ltd. The durability of the cured body was also measured at the same time as in the examples.
[0025] Evaluation results Table 3 shows the bending strength test results of the medical and dental composite resins prepared based on the examples and comparative examples. As is clear from these results, the medical and dental composite resins containing the functional fine particles produced by the present invention have clearly higher bending strength properties than the medical and dental composite resins using commonly used silane coupling agents (KBM-503, KBE-503). In addition, they are characterized by a high amount of energy until breakage. This is presumably because the surface treatment using a general silane coupling agent has a limit to its heating temperature, making complete dehydration and condensation difficult. In other words, it was difficult to completely eliminate the fragile xerogel layer. In response to this problem, the functional fine particles produced by the present invention have radical polymerizable groups introduced from the inorganic filler surface via urethane bonds, which are covalent bonds, so that it is possible to obtain a very dense surface treatment layer without any fragile xerogel layer. As is clear from the above results, it is now possible to provide medical and dental materials with high mechanical strength and durability that could not be achieved by conventional techniques.
[0026] [Table 1]
[0027] [Table 2]
[0028] [Table 3]
[0029] Compressive strength test in humid environment In Examples 1 to 5, the medical and dental hardenable compositions of the present invention were produced in an environment where the relative humidity of the laboratory was controlled at 50±5. In Examples 6 to 8, the medical and dental hardenable compositions of the present invention were produced in an environment where the relative humidity of the laboratory was controlled at 65±5%, 80±5%, and 95±5%, respectively. However, since the monomer for modifying the inorganic fine particles used in the present invention is an organic compound that has a radical polymerizable group at one end and generates an isocyanate group by heating, it is not affected by the relative humidity, and no statistically significant difference was detected in the physical property test results of Examples 6 to 8 compared to Example 1. In contrast, all of Comparative Examples 6 to 8 use a monomer (MOI) with an exposed isocyanate group. For this reason, it was concluded that the compressive strength results of the physical property test of the medical and dental hardenable compositions obtained tend to decrease as the relative humidity increases to 65±5%, 80±5%, and 95±5% when producing the medical and dental hardenable compositions. Furthermore, when the test results were subjected to an analysis of variance, it was found that there was a statistically significant difference between relative humidity and compressive strength.
[0030] [Table 4]
[0031] [Table 5]
[0032] [Table 6]
[0033] [Table 7]
[0034] Determination of silanol groups with trimethylchlorosilane The silanol groups react quantitatively and easily with trimethylchlorosilane due to their active hydrogen. In other words, it is possible to quantitatively determine the amount of silanol groups on the surface of inorganic fillers by adding a trimethylchlorosilane solution with a known concentration to a precisely weighed suspension of inorganic fine particles and quantifying the amount of remaining trimethylchlorosilane. The reaction proceeds smoothly if pyridine or other substances are added to remove the hydrogen chloride that is released and then removed from the system. The conceptual diagrams are shown below. Although not shown in the diagram, the hydrogen chloride that is produced precipitates out of the system as a pyridine salt.
[0035] [ka]
[0036] When the isocyanate group is deactivated by humidity and becomes a primary amine via carbamic acid, the silanol group forms a complex with the primary amine as shown in the figure below, and the number of active silanol groups is actually reduced. Therefore, the number of radically polymerizable groups finally introduced to the inorganic filler surface is limited. This is why the humidity in the comparative example leads to a decrease in the physical properties such as compressive strength of the final medical and dental hardenable composition. In addition, the radically polymerizable group (R in the figure) that forms a complex with the primary amine is a weaker bond than the urethane bond due to the σ bond, so it cannot contribute to improving the compressive strength.
[0037] [ka]
[0038] After leaving the inorganic filler for 10 minutes under each relative humidity in the table below, excess 2-isocyanatoethyl methacrylate was reacted in the presence of dibutyltin dilaurate and dehydrated toluene. Then, the bond between the primary amine and the inorganic filler complex was released by irradiating ultrasonic waves for 10 minutes with a 28KHz-150W ultrasonic disperser. After ultrasonic treatment, separation and decantation were repeated with a centrifuge to remove unreacted 2-isocyanatoethyl methacrylate. Then, excess chlorotrimethylsilane was reacted in the presence of dehydrated toluene and pyridine. After the reaction, the amount of unreacted chlorotrimethylsilane was quantified using a gas chromatograph equipped with a BID detector to quantify the amount of silanol groups complexed with the primary amine.
[0039] The table below shows the quantitative results of the silanol groups. Experiments 1 to 4 show the results using 2-isocyanatoethyl methacrylate, and Experiments 5 and 6 show the results using (E)-2-((((butan-2-ylideneamino)oxy)carbonyl)amino)ethyl methacrylate. As can be seen from the table, as the relative humidity increases, 2-isocyanatoethyl methacrylate becomes 2-aminoethyl acrylate via carbamic acid, and the primary amine forms a complex with the silanol group, inhibiting the reaction of 2-isocyanatoethyl methacrylate with the silanol group. Thus, the medical and dental hardening composition using the inorganic filler prepared using (E)-2-((((butan-2-ylideneamino)oxy)carbonyl)amino)ethyl methacrylate or 2-(3,5-dimethyl-1H-pyrazole-1-carboxamido)ethyl methacrylate, which is a compound that generates an isocyanate group by heating, showed higher physical properties than the medical and dental hardening composition using the inorganic filler prepared using the silanol group-reactive monomer with an exposed isocyanate group such as 2-isocyanatoethyl methacrylate.
[0040] [Table 8] [Industrial Applicability]
[0041] Generally, (meth)acrylic acid derivative monomers such as methyl methacrylate, triethylene glycol dimethacrylate, and urethane dimethacrylate are used in adhesives and composite resins. In the free radical polymerization (hereinafter referred to as radical polymerization) of vinyl monomers such as these (meth)acrylic acid derivative monomers, the carbon-carbon double bonds are cleaved to become single bonds, forming a polymer and hardening. In addition to vinyl monomers, inorganic fillers are added to this composite resin for the purpose of improving mechanical strength. In general, these inorganic fillers are surface-treated with silane coupling agents having polymerizable groups to improve wettability and mechanical strength. However, since these silane coupling agents have a carbon skeleton, there is a limit to the drying temperature, and the dehydration condensation of the generated silanol groups could not be completed. In other words, since it has a fragile xerogel layer, the current situation is that the mechanical strength is not as high as expected. Since the functional fine particles of the present invention have radical polymerizable groups introduced from the inorganic filler surface via urethane bonds, which are covalent bonds, it is possible to obtain a very dense surface treatment layer without any fragile xerogel layer. As is clear from the above results, it is now possible to provide medical and dental materials with high mechanical strength and durability that could not be achieved by conventional techniques. As such, the present invention overcomes all of the problems of conventional silane coupling agents, and it can be said that the present invention has great potential for industrial application.
Claims
1. A method for producing functional fine particles in which radically polymerizable groups are introduced via urethane bonds to hydroxyl groups or silanol groups on the surface of an inorganic filler, the method comprising the steps of: (1) A step of uniformly mixing an organic compound having a radical polymerizable group at one end and capable of generating an isocyanate group upon heating, and an inorganic filler. (2) A step of heating the mixture obtained in the step (1) to generate isocyanate groups. (3) A step of introducing radically polymerizable groups via urethane bonds into the isocyanate groups generated in the step (2) and the hydroxyl groups or silanol groups on the surface of the inorganic filler.
2. moreover, (4) removing the residue by-produced in the step (2); The method of claim 1, further comprising:
3. moreover, (5) A step of drying and removing the organic solvent and water coexisting with the inorganic filler obtained in the step (3); The method of claim 1, further comprising:
4. 2. The method for producing functional fine particles according to claim 1, wherein the organic compound having a radical polymerizable group at one end and generating an isocyanate group upon heating is selected from the following: 【Chemistry 1】 【Chemistry 2】 【Chemistry 3】
5. 2. The method for producing functional fine particles according to claim 1, wherein the organic compound having a radical polymerizable group at one end and generating an isocyanate group upon heating is selected from the following: 【Chemistry 4】
6. 2. The method for producing functional fine particles according to claim 1, wherein the inorganic filler is silicon dioxide, alumina, silica-titania, silica-titania-barium oxide, silica-zirconia, silica-alumina, lanthanum glass, borosilicate glass, soda glass, barium glass, strontium glass, glass ceramic, aluminosilicate glass, barium boroaluminosilicate glass, strontium boroaluminosilicate glass, fluoroaluminosilicate glass, calcium fluoroaluminosilicate glass, strontium fluoroaluminosilicate glass, barium fluoroaluminosilicate glass, or strontium calcium fluoroaluminosilicate glass.
7. 2. The method for producing functional fine particles according to claim 1, wherein the heating temperature in step (2) is in the range of 100° C. to 150° C. under atmospheric pressure.
8. 2. The method for producing functional fine particles according to claim 1, wherein in the mixing step (1) of claim 1, a dehydrated organic solvent having a water content of 50 ppm or less is added in an amount equal to or less than the mass of the inorganic filler.
9. 2. The method for producing functional fine particles according to claim 1, wherein the heating step according to step (2) of claim 1 is carried out in a pressure vessel with a pressure resistance of 10 MPa or less.
Citation Information
Patent Citations
Dental reparative material
JP1990134307A
Surface treatment of inorganic filler
JP1991070778A
Silane coupling agent, and composite resin for dental application and primer for dental application each comprising the silane coupling agent
JP2007238567A
New organosilicon compound, and composition comprising the same
JP2010229054A